SMALL MEDIUM MICRO BUSINESS STRATEGIES IN DEALING WITH THE IMPACT OF THE COVID-19 PANDEMIC - Putranto Hari Widodo; Neli Hajar; Laelatul Maghfiroh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Covid-19 pandemic is one of the viruses that threatens many lives and sectors throughout the world, one of which is Indonesia. Since the Covid-19 pandemic, one of the sectors most affected by the Covid-19 pandemic is the economic sector because social vulnerabilities make the position of economic resilience experience shocks. Many MSMEs experienced a decrease in income so that the impact was a lot of reduction in employees and even stopped operating. To be blea to survive and get out of the crisis, the presence of MSME Innovation is the right solution. This study discusses the application of innovations that need to be applied to MSMEs affected by the covid-19 virus, innovation from the marketing side, and product flexibility, rather than creating new products. This research relates to the theme of MSMEs only to describe and problems through the solution of related literature studies that have occurred in Indonesia, secondary data obtained from MSMEs in Central Java.